The Role of the International Monetary Fund and the World Bank in Financing small and Medium Enterprises in Iraq - Jassim, Sarin Faisal Ali; FAHAD, Aysar Y. (The journal of contemporary issues in business and government, 2022)
Monetary studies are currently being attended with interest by the various researchers’ economists, especially after the importance of monetary policies and their effective impact on economic activity and its growth rate have been confirmed. (Through affecting on the level of production, prices, labor, exchange rates, balance of payments conditions, distribution and redistribution of income and wealth in society and at the international level). Small and medium Enterprises (SMEs) Constitute the Backbone of an Economy. They not only provide employment and، there for income opportunities to a large number of people, but they are also at the forefront of technological in innovation and export diversification. the international monetary fund have several ways to get involved in SMEs finance, ranging from the creation or participation SMEs finance investment funds, to the creation of special unit for financing SMEs within institutions for this purpose.